2007
DOI: 10.2337/dc06-2184
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Surgical Mortality and Morbidity in Diabetic Patients Undergoing Cardiac Surgery With a Combined Intravenous and Subcutaneous Insulin Glucose Management Strategy

Abstract: OBJECTIVE -To determine if glucose management in postcardiothoracic surgery patients with a combined intravenous (IV) and subcutaneous (SC) insulin regimen reduces mortality and morbidity in patients with diabetes and stress-induced hyperglycemia.RESEARCH DESIGN AND METHODS -Retrospective review of 614 consecutive patients who underwent cardiothoracic (CT) surgery in 2005 was performed to evaluate the incidence and treatment of postoperative hyperglycemia and operative morbidity and mortality. Hyperglycemic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(138 citation statements)
references
References 20 publications
5
126
0
6
Order By: Relevance
“…Furnary et al (11) have shown that patients who had mean glucose levels of .150 mg/dL in the first 3 days after cardiac surgery have twice the infection rate and 13 times the mortality compared with normoglycemic patients. In our previous studies at Northwestern University (22,23), using intravenous and subcutaneous insulin regimens with the previous target glucose level of 80-110 mg/dL with a GMS consultation, we have shown that the postoperative complication rates for patients undergoing cardiac surgery were similar in diabetic and nondiabetic subjects, unlike the very high levels of complications in diabetic patients found by others when glycemic control was not achieved (14). van den Berghe et al (10) first reported a 42% reduction in mortality in surgical ICU patients (87% without diabetes) when they were randomized to an intensive control group (BG level 80-110 mg/dL) versus a conventional group (BG level ,180 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furnary et al (11) have shown that patients who had mean glucose levels of .150 mg/dL in the first 3 days after cardiac surgery have twice the infection rate and 13 times the mortality compared with normoglycemic patients. In our previous studies at Northwestern University (22,23), using intravenous and subcutaneous insulin regimens with the previous target glucose level of 80-110 mg/dL with a GMS consultation, we have shown that the postoperative complication rates for patients undergoing cardiac surgery were similar in diabetic and nondiabetic subjects, unlike the very high levels of complications in diabetic patients found by others when glycemic control was not achieved (14). van den Berghe et al (10) first reported a 42% reduction in mortality in surgical ICU patients (87% without diabetes) when they were randomized to an intensive control group (BG level 80-110 mg/dL) versus a conventional group (BG level ,180 mg/dL).…”
Section: Discussionmentioning
confidence: 99%
“…This new guideline recommended a BG target of 140-180 mg/dL, with 110-140 mg/dL being marked as acceptable in certain centers with considerable experience with such management. Because of our prior extensive experience and studies at Northwestern Memorial Hospital (NMH) demonstrating the safety of intravenous insulin protocols with a BG target of 80-110 mg/dL (22,23), we decided to change to the 110-140 mg/dL target. As a result, the intravenous insulin infusion and subcutaneous injection protocols used by our Glucose Management Service (GMS) at NMH were modified in 2009, so that the target BG levels for the intravenous protocol would be 110-140 mg/dL instead of 80-110 mg/dL, and the fasting and preprandial glucose levels during the subcutaneous insulin protocol would be 110-180 mg/dL instead of 80-150 mg/dL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Reduced morbidity and mortality from improved glycemic control in surgical patients also support the association between hyperglycemia and post-operative outcomes. [4][5][6][7][8][9] However, the risks of unrecognized hyperglycemia (in patients not known to have diabetes) prior to surgical operations remain unclear. Although Ramos et al have investigated associations between post-operative hyperglycemia and post-operative complications, 10 we were interested in using pre-operative blood glucose as a marker for post-operative complications in patients not known to have diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Once identified the association between diabetes and diabetes/infection with increased length of hospital stay, it is up to the managers the implementation of measures that are able to reduce these outcomes [21,23,30,31], aiming at cost reduction as already demonstrated in other institutions [22].…”
Section: Discussionmentioning
confidence: 99%